Dielectric and electric properties of Zn doped and undoped Bi2/3Cu3Ti4O12 ceramic prepared by chemical route - Rai V.S.; Singh N.B.; Mandal K.D. (My University, 2025)
Zn-doped and un-doped BCTO ceramics (Bi2/3Cu3−xZnxTi4O12, x = 0 and 0.05) were prepared by chemical route sintered at 1123 K for 8 h. The Phase formation of ceramics were confirmed by X-ray Diffraction. Their microstructural properties were examined through SEM, EDX, and TEM. The dielectric constant (ɛr) of BCTO ceramic was obtained higher than BCZTO-0.05 ceramics at 100 Hz and 470 K. The tangent loss (tan (Formula presented.)) value for Zn doped BCTO ceramics were found to be lower than undoped BCTO ceramics at 10 kHz and 310 K. The conductivity dependence of Bi2/3Cu3−xZnxTi4O12 ceramics (where x = 0, 0.05), with the inverse of temperature follows the Arhenius equation, with a major temperature range of 300–500 K. © 2023 Taylor & Francis Group, LLC.